180k views
2 votes
Simplify to create an equivalent expression. -3(2+4k)+7(2k-1)−3(2+4k)+7(2k−1)

User Liszt
by
5.1k points

2 Answers

1 vote

Answer:


Explanation:

-3(2+4k)+7(2k-1)−3(2+4k)+7(2k−1)=

-6-12k+14k-7-6-12k+14k-7=

4k-26

User Roger Gusmao
by
4.8k points
6 votes

Answer:

-26 +4k

Explanation:

-3(2+4k)+7(2k-1)−3(2+4k)+7(2k−1)

Notice that we have 2k-1 as a factor 2 times and 2+4k as a factor 2 times

-3(2+4k)−3(2+4k)+7(2k−1)+7(2k-1)

Think of the factor as a variable 2k-1 = M and 2+4k = P

-3(P)−3(P)+7(M)+7(M)

Combine like terms

-6P + 14M

Now substitute back M =2k-1 and P = 2+4k

-6(2+4k) +14 (2k-1)

Distribute

-12 -24k + 28k -14

Combine like terms

-26 +4k

User Rune Kaagaard
by
5.9k points